"Caroline & Hermann" - pierwsza kopalnia węgla brunatnego na tle górnictwa Ziemi Lubuskiej = "Caroline & Hermann" - the first lignite mine against Lubusz land mining - Gontaszewska-Piekarz, Agnieszka (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents history of the oldest mine in the region Ziemia Lubuska (West Poland), i.e. ?Caroline & Hermann? in Glisno near of Sulęcin. Paper also describes the discovery of lignite deposits in the nineteenth century near Sulęcin and gives available information about beginnings of lignite mining in Ziemia Lubuska.
Keywords: Glisno; górnictwo węgla brunatnego; kopalnia węgla brunatnego; historia górnictwa; lignite mining; lignite mine; mining history